DESAIN PENDIDIKAN AGAMA ISLAM MULTIKULTURAL DI PONDOK PESANTREN ZIYADATUT TAQWA PAMEKASAN - Hair, Moh Afiful; Wahyuni, S (Al-Ulum Jurnal Pemikiran dan Penelitian ke Islaman, 2023)
Indonesia consists of various tribes, cultures, races, religions and various languages ​​or is usually called a plural nation. This is certainly an added value and a challenge for the Indonesian people in forming a safe, peaceful, peaceful and prosperous society free from conflict and division. Islamic boarding schools are places of learning for students from various ethnic, cultural, racial and linguistic backgrounds. As an initial bulwark to prevent conflict and division, Islamic boarding schools need to develop a multicultural Islamic religious education curriculum. This research uses a qualitative approach with empirical methods and descriptive narrative research. Data collection uses participant observation, unstructured interviews, and documentation by checking the validity of the data using triangulation of sources and methods. The data analysis used is data reduction, data presentation and drawing conclusions. The result of this research is that the design of a multicultural Islamic religious education curriculum is integrated into four Islamic boarding school programs, namely: the Ma'hadiyah program, which includes Islamic boarding school activities such as the study of classical books, tahlil, dhikran, and so on which contains the teachings of Sunnah wal Jama'ah experts. Madrosiyah program, including learning activities such as Madrasah Diniyah, TPQ, and so on. The ubudiyah program is related to worship such as congregational prayers and worship taught by clerics who are experts in Sunnah wal Jama'ah and tahfiz al-Qur'an. The implication of this research is that education implementers can definitely know that multicultural education is important for students so that they understand the meaning of togetherness and mutual respect, mutual respect in creating a harmonious life among religious communities.